PRETREATMENT OF BIOGAS PRODUCTION BYPRODUCTS - Božko, Margarita; Teirmunieka, Ērika (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
“Pretreatment of Biogas Production Byproducts”. The aim of the research is to determine the optimal method of hydrogen sulphide attraction at the biogas production station and elaborate a solution for digestate treatment from microbiological pollution. Out of nine researched regents the best one to attract hydrogen sulphide in the biogas reactor is Fe2O3·3H2O, Fe(OH)3, AlCl3. From the point of view of the environmental safety the safest are Fe2O3·3H2O, Fe(OH)3, from the point of view of costs the cheapest are Fe2O3·3H2O and AlCl3. It is suggested to use Fe2O3·3H2O as a regent for the attraction of hydrogen sulphide. The recommended optimal conditions for liquid digestate pasteurization at the biogas production station are: thermal treatment at 70 ºC, time of treatment 60 minutes or thermal treatment at 80 ºC, time of treatment 30 minutes.